3D-Printed Green Biocomposites from Poly(lactic acid) and Pine Wood-derived Microcrystalline Cellulose: Characterization and Properties - Selwin Maria Sekar; Rajini Nagarajan; Ponsuriyaprakash Selvakumar; Nadir Ayrilmis; Kumar Krishnan; Faruq Mohammad; Hamad A. Al-Lohedan; Sikiru O. Ismail (BioResources)
The increasing demand for sustainable and high-performance materials has prompted research into biocomposites as eco-friendly alternatives to traditional plastics. Poly(lactic acid) (PLA), which is widely used, often lacks the mechanical and thermal stability required for advanced applications. This limitation can be overcome by reinforcing PLA with microcrystalline cellulose (MCC), a renewable and abundant resource. While existing PLA composites have shown promise, the uniform dispersion and interfacial bonding of reinforcements remain challenges. To bridge this gap, an optimal 80:20 wt% PLA/MCC ratio was identified and processed into filament using a single-screw extruder, followed by 3D printing via fused filament fabrication (FFF). The composite’s properties were evaluated through mechanical, thermal, and morphological analyses. Results revealed significant enhancements: tensile strength increased by 30%, flexural strength by 22.3%, impact strength by 78.9%, and compressive strength by 21.3%, compared to neat PLA. Thermogravimetric analysis showed improved thermal stability, with reduced weight loss at elevated temperatures. This research demonstrates that the integration of MCC into PLA not only improves mechanical and thermal properties but also offers an environmentally sustainable solution for engineering applications. The findings highlight the potential of PLA/MCC composites for industries requiring lightweight, durable, and eco-conscious materials, including automotive and biomedical sectors.